Pengaruh Religiusitas, Sosialisasi Perpajakan dan Kualitas Pelayanan Pajak Terhadap Kepatuhan WP Dengan Kesadaran WP Sebagai Variabel Intervening - Pulungan, Dedy Zakaria; Arifin, Syamsul Bahri (Jurnal Ekonomi Bisnis Digital, 2022)
Taxpayer compliance is very important in the country's economic development which has an influence on the welfare of the community, so there needs to be motivation and encouragement fromthe tax authorities who can improve taxpayer compliance. This study aims to determine the factors that affect taxpayer compliance. The population used in this study were all individual taxpayers who were registered as mandatory SPT at KPP Pratama Medan Timur as many as 51,191, with the slovin method.The results of this study indicate that religiosity and taxation socialization have no significant effect on Taxpayer Awareness, while Tax Service Quality has a significant effect on Taxpayer Awareness. Religiosity has no significant effect on Taxpayer Compliance, while Tax Socialization, Tax Service Quality, Taxpayer Awareness have a significant effect on Taxpayer Compliance. Taxpayer awareness cannot mediate the influence of religiosity, tax socialization and tax service quality on taxpayer compliance at KPP Pratama Medan Timur.